Music and Folkloristic Activities of Zdenek Kaspar, a Wallachian Musician and Collector - Chumchal, Jan; Kusak, Jiri (Aura musica, 2016)
The study focuses on the personality of a musician, teacher, arranger and collector of Wallachian folk songs. It primarily deals with his collecting and publishing activities related to the issues of music and folkloristics. The first part of the study defines the region of Wallachia in the context of Moravia and describes Zdenek Kaspar's personality. The second and third part deal with his collecting activities and subsequent publications of music and folkloristic articles in various periodicals.
Keywords: Zdenek Kaspar; collecting activities; publishing activities; Wallachia; folk song; musical folklore; the folklore company of Jasenka